The transmission of 'The West Saxon Royal Genealogy': a phylogenetic approach. - Sparks, Nicholas A; Windram, Heather F; Howe, Christopher J (Digital Scholarship in the Humanities, 2023)
We present a case study in the application of phylogenetic and other computational analyses to an Old English textual tradition. We chose the West Saxon royal genealogy for investigation because there are interesting problems in ascertaining the transmission of the text. We present a concise, up-to-date account of the manuscript tradition, a summary of the scholarly literature including current debates, and discuss phylogenetic and other analyses used to explore the tradition. We show how the results from phylogenetic analysis are consistent with interpretations advanced by scholars based on traditional methods of textual criticism. We also suggest a new textual grouping not mentioned before in the literature, and thus offer a new insight into this tradition. The suggested textual relationship finds support on historical and palaeographical grounds, and on that basis, we postulate the existence of a lost eleventh-century exemplar from Canterbury. The value of this article therefore lies in two main directions: first, we demonstrate the value of employing a combination of phylogenetic and other computer-based analysis methods with an Old English tradition; and second, we offer a striking new insight into the transmission and textual history of an important medieval English text.